Methodologies for decolonising geography curricula in the secondary school and in initial teacher education (UCL Press, 2022)
While a clear rationale for the need to decolonise school geography curricula has been proposed, there are few examples of what this looks like in practice. Drawing on our professional practice in both a secondary school and a university setting, we outline two case studies of decolonising the curriculum that centre on promoting student agency. The first is a Year 7 geography unit of work, and the second is a walking tour of London for an initial teacher education programme for secondary school geography teachers. Through these case studies, we argue for the importance of encouraging students to think about geographical relations with other places, and build on studies which foreground the importance of place as a pedagogic device through which the aims of decolonisation can be furthered.